(untitled) (Mustansiria Dental Journal, 2018)
Back ground: Poor oral health can have a profound effect on general health and the quality of life, the experience of pain, endurance of dental abscesses, problems with eating, chewing, and missing, discolored or damaged teeth, has a major impact on people’s daily lives and wellbeing. All these problems can be prevented by good personal oral hygiene practices. Objectives: The aim of this study was to find out the knowledge and practices of oral hygiene methods and assess any association between these methods with the prevalence of dental caries among the students in different colleges in Baghdad Methods: -Study design: Cross sectional -Study period: The study was conducted from September, 1st to December, 31st 2005 -Settings: Different colleges in Baghdad -Participants: A convenience sample of Four hundred and seventy students, male 236 (50.2%) and female 234 (48.8%). -Data collection: The data were collected by using a specially prepared questionnaire and oral examination. Results: 73.6% shows a poor and intermediate knowledge and practices methods of oral hygiene, the prevalence of dental caries reaches 66.4%. The proportion of dental carries among students with excellent score for the knowledge and practice methods of oral hygiene was 15.4 % (4 out of 26) only, while those with poor score showed 97.4% (76 out of 78). Conclusions: There is a need to enhance the knowledge of oral health and disease among our students, early detection and treatment of dental and oral diseases.